PERENCANAAN KEBUTUHAN LUAS RUANG PENYIMPANAN DAN KEBUTUHAN RAK ATAU ROLL OâPACK UNTUK REKAM MEDIS AKTIF SELAMA LIMA TAHUN KEDEPAN DI RUMAH SAKIT MATA âDr.Yapâ YOGYAKARTA - , ASRI NURJANAH ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Background Of Problem: Based on preliminary study by researchers to know the neccessary of Roll O 'Pack for the storage of active medical records, it is known that the active medical record storage has exceeded the limit and result in file medical records crammed in the Roll O' Pack allowing damage file or even torn. Purpose:Planing necessary active medical record room for five years later. Methods of research: the type of the research used is a qualitative description with cross sectional design. In this study, researchers will conduct research about neccessary of Roll O 'Pack for the storage of active medical records at Rumah Sakit Mata âDr.Yapâ Yogyakarta hospital. Results: For calculation of required number of Roll O'Pack there are 2 alternatives with each area of the room for the first alternative 1474.72 m2 with 5 Roll O'Pack alternative type I and II 262.08 m2 with 1 unit Roll O'Pack type II , 1 open shelf static 1 front, 1 shelf static open 2 front and 5 Roll O'Pack type I.